An investigation on donor funding on the performance of goal Zimbabwe - Saruchera, Alfred Tichaona (Midlands State University, 2017)
The study sought to investigate on donor funding on the performance of Goal Zimbabwe. The study was prompted by the noted decrease in funds, decrease in donors and increasing administration costs during the period 2012 to 2015. The research explored a body of literature for a further exhaustive knowledge of donor funding policies that the company may adopt to solicit funds and ensure survival as the industry is now characterized with great competition. The research conducted a census of 31 respondents to gather information of relevance to Goal Zimbabwe and utilized questionnaires and interviews to gather data. Questionnaires were 80.65% successful and 19.35% unsuccessful and three interviews were conducted. Graphical presentations, the mode statistical technique and data from literature was used to aid the analysis of results. From the findings of the research, though policies are in place Goal Zimbabwe is failing the competition and its relationship with INGOs is marred. This is because of lost trust, inadequate personnel, no provision of personnel development. The researcher then recommended active recruitment and selection of qualified personnel, personnel development, involving personnel in strategic planning, consider changes in development approaches, and maintain good relationship with INGOs.